Synergistic antibacterial activity of Lactococcus lactis and Xylella phage MATE 2 for an effective biocontrol strategy against black rot disease in broccoli - Sabri, Miloud; El Handi, Kaoutar; El Tousy, Abderrahim; De Stradis, Angelo; Elbeaino, Toufic (Frontiers in Microbiology, 2024)
Black rot, caused by Xanthomonas campestris pv. campestris (Xcc), is considered the most destructive disease affecting cruciferous vegetables, resulting in significant losses worldwide. The need for biocontrol agents against Xcc that can reduce reliance on chemical pesticides, enhance sustainability, and ensure crops and environmental health is crucial. Combining phages with other antibacterial agents (i.e., antibiotics and bacteriocins) to treat bacterial infections is gaining increased attention due to the frequently observed synergistic effects. This study introduces for the first time the combination of a lytic phage, i.e., Xylella phage MATE 2 (MATE 2) with nisinproducing Lactococcus lactis subsp. lactis (L. lactis) bacterium as an eco-friendly, cost-effective, and practical strategy for controlling Xcc in cruciferous vegetables. The antibacterial efficacy of MATE 2 and L. lactis, individually and in combination, against Xcc was investigated through a series of in vitro assays and in planta experiments conducted on broccoli plants. The time-killing curves results showed that under conditions of reduced Xcc population concentration (10 3 CFU/mL), MATE 2 at 10 8 PFU/mL exerted a persistent inhibitory effect on Xcc growth for 7 days. The Spot assays and v-qPCR analysis showed that both L. lactis and its bacteriocin nisin have significant antibacterial potential to contrast Xcc. Furthermore, combined application of MATE 2 and L. lactis in broccoli plants by foliar spraying generated significant synergistic efficacy in preventing Xcc infections, achieving a 71% reduction in symptoms, compared with 64% and 38% for single applications, respectively. In this study, the positive synergistic effect of the combined application of phage and beneficial bacteria in preventing black rot disease underscores this eco-friendly and cost-effective approach as a promising control measure against plant bacterial diseases.